Mites (Acari, Oribatida, Nanhermannidae) from the Eocene of Patagonia: First Southern Hemisphere Fossil Record in Marine Sediments - Fernández, Damián Andrés; Martínez, Pablo A.; Palazzesi, Luis; Barreda, Viviana Dora (Ameghiniana)
Cosmopolitan, abundant, and adapted to nearly all terrestrial environments today, mites are uncommon in the fossil record. Extant diversity of mites is second only to that of insects. With some 50,000 species described, of which nearly 25% are oribatids, their past diversity is not well reflected in the fossil record because of their rarity as fossils, especially in marine deposits and older strata (Selden et al., 2008). Mites are more abundant in Quaternary sites (e.g., Woolley, 1969; Elias, 1994; Heyne & Coetzee, 2001) and are being used in biostratigraphic and paleoclimatic studies of that period (e.g., Erickson, 1988; Schelvis, 1990; Erickson et al., 2003; Krivolutsky & Sidorchuk, 2003; Mauquoy & van Geel, 2007; Demske et al., 2013). A few are known from Cenozoic ambers (e.g., Selden et al., 2008 and references therein; Dunlop et al., 2013; Khaustov, 2014; Klimov et al., 2019; Poinar, 2019; Sidorchuk et al., 2019; Stilwell et al., 2020). Mites from Cretaceous ambers are far fewer in number (e.g., Selden et al., 2008 and references therein; Judson & Mąąkol, 2009; Sidorchuk et al., 2015a; Sidorchuk & Behan-Pelletier, 2017; Arillo et al., 2018 and references therein). The only record from South America until now is a large parasitengonid mite (Acari, Erythraeoidea) from the continental Early Cretaceous Crato Formation of Brazil (Dunlop, 2007). There are three oribatids known from the Jurassic (Krivolutsky & Krassilov, 1977; Sivhed & Wallwork, 1978; Selden et al., 2008), and only two species from Triassic amber, northeastern Italy (Sidorchuk et al., 2015b). The oldest known mite fossils come from the Devonian localities of Gilboa, USA (Norton et al., 1988; Kethley et al., 1989) and Rhynie, Scotland (Hirst, 1923). Fil: Fernández, Damián Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y ...